The Effect of Targeted Monetary Policy on Bank Lending - Olli-Matti Laine (Journal of Banking and Financial Economics)
This paper studies the effect of central banks’ targeted refinancing operations on bank lending. It utilizes data from the European Central Bank’s targeted longer-term refinancing operations (TLTROs) together with monthly bank level balance sheet data from multiple countries. The effect of targeted policy is identified utilizing the institutional setting that provides natural instrumental variables and a proxy for credit demand. Unlike previous papers, this paper studies the effects on corporate loans and loans for consumption separately. The cumulative effect of TLTROs on participating banks’ stock of corporate loans is estimated to be significant (about 20 per cent). However, the effect on lending for consumption is found close to zero. Furthermore, the positive effects on corporate loans are found to be driven by crisis countries suggesting that the effectiveness of monetary policy depends on the economic conditions. The paper also finds some evidence that the effect on government bond purchases is negative. This result is very different from the earlier results regarding non-targeted liquidity operations.